Pengaruh Perbandingan Eceng Gondok Dan Air Terhadap pH, Alkalinitas, Dan Total Asam Volatil Pada Produksi Biohidrogen Secara Fermentasi Anaerob Tahap Asidogenesis - Sari, Devita Ulfa; Muria, Sri Rezeki; Ahmad, Adrianto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Water hyacinth is one of aquatic weeds that commonly found in water and it grows very fast. Water hyacinth contains fermentable material, named cellulose and hemicellulose and it can be potentially used as a material for bioenergy as biohydrogen. Biohydrogen was produced from water hyacinth using microoorganism derived from cow manure by anaerobic batch fermentation. This research was originally purposed to produce biohydrogen and to determine the optimum water hyacinth to water ratio in their impacts on pH, alkalinity, and volatile fatty acid. Biohydrogen production occurred in three steps: seeding, acclimatization, and anaerobic batch fermentation. Water hyacinth to cow manure ratio was 75%: 25%. Anaerobic fermentation was carried out with variations of water hyacinth to water ratio 1:2, 1:3, 1:4 and 1:5 at initial pH 6 and mesophilic temperature. The most optimum water hyacinth to water ratio in this study was 1:2 with 3.45% biohidrogen product of total biogas.Keywords: anaerobic batch fermentation, biohydrogen, cow manure, water hyacinth